The Impact of COVID-19 on the Financial Performance of Insurance Companies in South Africa - Zungu, Siphesihle Charles; Maama, Haruna; Mvunabandi, Jean Damascene (Universitas Prasetiya Mulya, 2025)
The research aims to examine the influence of the Covid-19 pandemic on the financial performance of insurance companies in South Africa. The research sample comprises 37 insurance companies that are duly registered with the Financial Sector Conduct Authority (FSCA). The research used a descriptive analytical technique, focusing on quantitative and numerical data from annual financial reports published by insurance companies. The data was used to assess financial performance indicators over a time period of six consecutive years (2017–2022). The study indicated that Covid-19 had diverse impact on the financial performance of insurance companies. The financial performance was assessed using the metrics of return on assets (ROA) and return on equity (ROE). The study demonstrates a positive and statistically significant correlation between COVID-19 and ROA, shown by a coefficient of 2.642 and a p-value of 0.000. This conclusion indicates that, despite the obstacles posed by the pandemic, several insurance companies adeptly managed their assets to maintain profitability, possibly by using operational efficiency or capitalizing on market dynamics altered by the pandemic. Conversely, the findings demonstrate a negative correlation between COVID-19 and ROE (-0.15, p-value 0.008), underscoring the strain on equity returns, potentially attributable to elevated claim payments, diminished investment income, or intensified regulatory and stakeholder pressures during the crisis.